Rapid Multiorgan Dissemination of Low-Grade Myxofibrosarcoma: A Case Report - Yasutaka Murahashi; Mitsunori Kaya; Tamotsu Soma; Mikito Sasaki; Satoshi Nagoya; Takuro Wada; Toshihiko Yamashita (Case Reports in Medicine)
Myxofibrosarcoma is one of the most common sarcomas in the extremities of elderly people. It is characterized by a high frequency of local recurrence due to an infiltrative growth property. In contrast, the overall risk of distant metastases is generally low. This makes the prognosis for the patients with myxofibrosarcoma definitely good. In this paper, we will report the case of a 79-year-old female with very aggressive metastatic low-grade myxofibrosarcoma. The disease progression was really unexpected and misled every possible medical interpretation, leading to rapid worsening of the patient's clinical conditions and no chance for therapy. The tumor developed diffuse infiltration in lung, spine, skeletal bone, abdomen, paravertebral muscles, and liver. The patient died 8 months after the diagnosis of remote metastases due to rapid tumor progression.